Doctor-Patient communication among Interns at a tertiary care medical college and hospital in eastern India - Dharmendra Kumar; Tanay Sinha; Swapan Kumar Paul; Piyali Dutta Chowdhury; Ranabir Pal (Al Ameen Medical College, 2021)
Background: There is supreme importance for teaching-learning among Interns regarding their perception on Doctor-Patient relationship based on Doctor-Patient communication. Objectives: To find out the perception of Interns regarding Doctor-Patient Communication. Methods: A hospital-based prospective open-label observational cross-sectional study was conducted among interns to assess the perception and correlates based on distinguished questions on Doctor-Patient Communication at the emergency, out-patient and in-patient departments, at a medical college and hospital in eastern India during March to May 2021. Results: The perception of the Interns regarding the reported expectation of patients was positive, while Interns' self-satisfaction after independently managing the patients could assess the strength of mutual communication. On the Interns' perception regarding expectation of patients, all the responses were in favour of them except 'time constraints' and 'general advice'; all were statistically highly significant. On the Interns' reported satisfaction after independently dealing with the patients, majority of responses favoured Intern's positive approaches of calm hearing, addressing complaints and caring patient's view; yet, private matters and other issues of the patients were not satisfactorily addressed; these responses were highly significant. On critical analysis, the Interns were satisfied while communicating with the patients amid increased stress, workload and patient load; Interns were content on patients' compliance which was statistically significant. Conclusions: This study revealed the most updated observation on interns' perception regarding Doctor-Patient communication on a positive note and their satisfaction.